Measuring the impact of calorie labeling: The mechanisms behind changes in obesity. (28th August 2021) - Aranda, Rodrigo; Darden, Michael; Rose, Donald
Abstract: Learning the true calorie content of fast food may induce consumers to change behavior, yet recent evidence is mixed on whether calorie labels cause consumers to order healthier meals. Especially for individuals for whom consumption of highly caloric fast‐food is habitual, a rational response to calorie labeling may instead be to maintain consumption levels but increase physical activity. Using American Time Use Survey data from 2004 to 2012, we show that the 2008 New York City Calorie Labeling Mandate significantly improved several measures of physical activity, including overall metabolic equivalents of task units and minutes of sedentary activity. Our results translate to an average extra 28 calories burned per day or a 0.6 kg weight decrease for the average person over one year. These results provide a plausible mechanism for calorie labeling mandates to lower obesity rates, which we demonstrate in the New York City context.